MANAGING OF UNIONISED AND NON-UNIONISED TEACHERS IN SCHOOLS - Dr.Nozipho Isabel Adaghe; Prof.Vimbi Petrus Mahlangu (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This article looked at how schools handle both unionized and non-unionized teachers. Understanding the administration of human resources, which heavily relies on the feelings, actions, and attitudes of principals as managers, was done through the lens of the theory of emotional intelligence. This article's research design was an interpretive case study that was qualitatively analyzed. The interpretivism paradigm is appropriate for the research design used in this work. According to the interpretivist paradigm, social reality is produced by individuals' irrational perceptions of their surroundings. Since focus is placed on hearing the participants' voices, a qualitative method is defined by its capacity to convey the opinions and viewpoints of participants. The qualitative methods of focus groups, observations, and interviews were employed to create this paper. Aside from their primary objective of ensuring that teaching and learning occur effectively at school, one of the key responsibilities of principals is the management of the two categories of teachers who work there: unionized and non-unionized. It is generally known that finding and putting into practice the ideal management techniques for these teachers is a monumental effort for principals. An assessment of current management techniques demonstrates the need for new management techniques to address the issues that administrators are having with managing these teachers. There are several ways to put these new tactics into practice. Among these techniques is building trust between principals and teachers through effective communication and involvement in decision-making.